Devolution as a means of expanding local forest management in South China - Liu Dachang; Edmunds, D. (Resources for the Future and Center for International Forestry Research, 2003)
This chapter describes the change in the institutional arrangements for property rights to the former collective forest lands and the sifts in oversight responsibility for these lands from central to regional and local governments. The data rely on national forest survey data and the authors' own research experience in 22 villages in China's South and Southwest to illustrate the impacts of these changes. The effects of reforms have changed over time; for example, from initial period of rapid deforestation in early 1980s to gradual reforestation and forest groth in the 1990s. There are variation in impacts between households and between regions and the authors suggest some of the remaining opportunities for policy reform in the sector. Despite the devolution of authority and the growth in both forestland and forest stock, investments in forest management remain more constrained than those in comparable agricultural activities. Individual households now posses the rights to the products of their household plots, and most of the controls on the inputs of productive activities were removed by the late 1980s, but the local bureaus maintain the right to limit harvest levels and shipments of forest products. Various levels of government also impose an array of timber taxes and charges that account for more than 50% of the market value of timber in some provinces. The relevant agencies began increasing these fees shortly after timber prices began to rise in response to market liberalization in 1985. The agencies saw an opportunity to increase their own revenues, and take advantage of it. Since then, taxes and charges have risen more rapidly than timber prices.